O ensino religioso como instrumento para minimizar as desigualdades sócio-educacionais no contexto escolar - Abreu, Gilton Barbosa de (2009)
The current society has been giving primacy to property and technology, being so illuminated in knowledge and so dark in spiritual sense. The Religious Teaching in public schools should work discussing and looking for solutions, because we verify the erosion of moral values. This provokes us to invoke justice, peace and an education which stimulates the critical sense to the base of the question, as Christ made. It is in this way that we suggest a curriculum of Religious Teaching in public schools which works social justice, tolerance, peace and the rescue of values.